A reference grammar of Chinese - Huang, Chu-Ren; Shi, Dingxu (Cambridge University Press, 2016)
"A Reference Grammar of Chinese is a comprehensive and up-to-date guide to the linguistic structure of Chinese, covering all of the important linguistic features of the language and incorporating insights gained from research in Chinese linguistics over the past thirty years. With contributions from twenty-two leading Chinese linguists, this authoritative guide uses large-scale corpora to provide authentic examples based on actual language use. The accompanying online example databases ensure that a wide range of exemplars are readily available and also allow for new usages to be updated. This design offers a new paradigm for a reference grammar where generalizations can be cross-checked with additional examples and also provide resources for both linguistic studies and language learning. Featuring bilingual term lists, this reference grammar helps readers to access relevant literature in both English and Chinese and is an invaluable reference for learners, teachers and researchers in Chinese linguistics and language processing. A Reference Grammar of Chinese is a comprehensive and up-to-date guide to the linguistic structure of Chinese, covering all of the important linguistic features of the language and incorporating insights gained from research in Chinese linguistics over the past thirty years. With contributions from twenty-two leading Chinese linguists, this authoritative guide uses large-scale corpora to provide authentic examples based on actual language use. The accompanying online example databases ensure that a wide range of exemplars are readily available and also allows for new usages to be updated. This design offers a new paradigm for a reference grammar where generalizations can be cross-checked with additional examples, and also provide resources for both linguistic studies and language learning. Featuring bilingual term lists, this reference grammar helps readers to access relevant literature in both English and Chinese and is an invaluable reference for learners, teachers, and researchers in Chinese linguistics and language processing" -- Provided by publisher.